Dual catalytic systems for cross dehydrogenative coupling toward donor-acceptor conjugated polymer synthesis - Xing, Liwen (My University, 2022)
Donor-acceptor (D-A) conjugated polymers, as one type of organic semiconducting materials, have drawn lots of attention for the application in organic electronics due to their lowered band gaps and high charge mobility. The polymerization based on cross dehydrogenative coupling (CDC) is an atom-economic synthetic method for D-A polymers as it significantly simplifies the overall synthetic routes by applying C-H bond activation during the polymerization. Two different dual catalytic systems – Au/Ag and Pd/Ag for CDC polymerizations were investigated here. Despite both transformations occurring by a similar mechanistic sequence, dramatically different kinetic behaviors and polymerization results were discovered. The Pd/Ag system produced unexpectedly low homocoupling defects and high molecular weight polymers despite the small molecule coupling reaction proceeding inefficiently. Conversely, Au/Ag system produced low molecular weight polymers with lots of homocoupling defects while catalyzing an efficient small molecule coupling reaction. While the findings in this work provide valuable insight for future studies in obtaining high-molecular weight D-A polymers via CDC, these findings could affect the design of substrates in late-stage C−H functionalization.
Thesis (Ph.D.)--University of Washington, 2022
Keywords: C-H activation; Conjugated polymers; Cross dehydrogenative coupling; Dual transition metal catalysis; Polymer chemistry; Chemistry; Materials Science; Molecular engineering